STUDENTS’ PERCEPTION USING VIDEO CONFERENCING PLATFORM IN LEARNING ENGLISH DURING ONLINE LEARNING - Hanas Ulfah Safitri; Peptia Asrining Tyas (English Language Education Department, Universitas Majalengka, 2022)
Video conferencing is one of the most common technology platforms for emergency online learning during the Covid-19 outbreak. Therefore, this study investigates students' perceptions of video conferencing for online English learning and video conferencing platforms as a media technology. This study involved 103 students in the second, fourth, and sixth semesters of the English Language Education Program at Universitas Brawijaya in 2021/2022 who used a video conferencing platform to study English online. In this study, a quantitative approach involving survey research was applied. A closed-ended questionnaire was used to collect the data, and descriptive statistics were used to analyze the results. The data were collected using a 19-question divided into two categories: (1) students' perceptions of using video conferencing in learning English during online learning and (2) students' perceptions of video conferencing platforms as a media technology. The findings indicate that video conferencing facilitates English learning during online education, and the solutions can help students improve their English language skills. In addition, the majority of students responded positively to the use of video conferencing during online learning in learning English.